Exploring rice varietal effects on triglyceride/high density lipoprotein ratio in hyperlipidemia-induced wistar rats - Rosmalinda, Yusie; Noer, Etika Ratna; Sulchan, Mohammad; Khikmaturrohman, Sya’bani Isnaen; Ardiaria, Martha; Marsa, Firdaus Shadiqa; Henny, Via Anugrah; Wijayanti, Hartanti Sandi; Panunggal, Binar (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Excessive intake of white rice has been associated with elevated triglyceride (TG) levels and decreased high density lipoprotein (HDL) cholesterol concentrations. Conversely, black and red rice varieties have demonstrated favorable impacts on lipid metabolism. However, despite these benefits, their palatability and texture are often met with aversion by consumers. Consequently, it is imperative to investigate rice blends that are both well-received by individuals and exhibit pronounced efficacy in reducing the TG/HDL ratio.Objective: To investigate the differential effects on the TG/HDL ratio in rats administered different combinations of white, red, and black rice.Methods: This research follows a true experimental design incorporating pre- and post-tests with a control group. Thirty rats were initially fed a hyperlipidemic diet for 14 days. Subsequently, the rats were subjected to interventions involving different rice combinations for a duration of 28 days. These combinations included K(+) (positive control), P1 (100% white rice), P2 (21 g red and 4 g white rice), P3 (16 g black and 4 g white rice), and P4 (8 g black, 8 g red, and 4 g white rice). Triglyceride and HDL levels were quantified using the GPO-PAP and CHOD-PAP methods, respectively. Statistical analysis was performed utilizing ANOVA tests followed by LSD post-hoc tests for comparison.Results: Triglycerides decrease in P4 (-51.04±0.72) was the highest, followed by P3 (47.18±0.51), P2 (-34.60±1.07), P1 (-17.03±1, 06). Cholesterol HDL increase in P4 (49.36±1.68) was the highest, followed by P3 (42.71±0.41), P2 (38.09±0.76), P1 (30.64±0.90). The TG/HDL ratio in P1, P2, P3, and P4 were 0.21±0.092, -2.12±0.164, -2.45±0.123, -2.82±0.148, -3.18±0.371, respectively. The rice combination intervention had a significant decreased on the TG/HDL ratio (p=0.000).Conclusion: The intervention involving rice combinations resulted in a greater reduction in the TG/HDL ratio compared to the consumption of white rice alone. Among the various combinations tested, the combination of white, red, and black rice demonstrated the most significant reduction in the triglyceride to HDL-cholesterol (TG/HDL) ratio.